One welfare: bibliometric review of world literature - Platto, Sara; Normando, Simona; Serres, Agathe; Manteca, Xavier; Temple, Deborah (Frontiers in Veterinary Science, 2025)
The One Welfare framework emphasizes the interconnection between animal, human, and environmental well-being, extending One Health principles to address broader welfare dimensions. Despite its relevance, One Welfare remains underexplored. This study investigates global research trends and thematic priorities in One Welfare literature published from 2013 to 2024. A bibliometric review was conducted using PubMed, Elsevier, Springer, Web of Science, Scopus, and CABI databases. A literature search was conducted using keywords translated into five of the world’s most widely spoken languages: Hindi, Chinese, Spanish, English, and French. A total of 111 publications were identified and categorized into four main domains—Policy, Governance, Economy (PGE); Applied Human-Animal Sciences (AHAS); Societal, Economic, Environmental Dimensions (SEED); and Human-Animal Bond and Mental Health (HAB-MH)—and eight subcategories: Legal Framework and Economy (LFE); Education and Philosophy (EP); Sustainable Resource Management (SRM); Traditional Knowledge and Societal Impact (TKSI); Animal Management (AM); Human-Animal Diseases (HAD); Human-Animal Interaction (HAI); and Psychology (PSY). The analysis also considered animal types—companion animals (CA), production animals (PA), wild animals (WA), working/sport animals (WS), and general (GE)—and divided data into two time periods (2013–2018, 2019–2024). Most publications (78) emerged after 2018, with Animal Management (AM) subcategory as the dominant theme, particularly in relation to PA reflecting their significance in food security. Human-Animal Interaction (HAI) was the second most represented theme among the subcategories, particularly in relation to CA underlining their significance in human lives. Conversely, wild animals (WA), climate change, and working/sport animals (WS) remain underrepresented. Education and Philosophy was the least addressed subcategory, exposing a critical gap in integrating One Welfare into veterinary and animal science education. Given the limited number of publications identified over the past 11 years, there is a clear need to promote increased interdisciplinary research, policy development, and educational reform to fully implement the One Welfare framework and align it with global sustainability goals.